The Influence of Product Innovation and Service Innovation on the Saving Interest of the Millennial Generation at Bank Syariah Indonesia KCP Cemara Asri - Dea Amanda Putri; Aqwa Naser Daulay; Nur Ahmadi Bi Rahmani (Amkop Management Accounting Review (AMAR), 2025)
This study analyzes the effect of product innovation and service innovation on the saving interest of the millennial generation at Bank Syariah Indonesia KCP Cemara Asri, Medan. The scope of the study focuses on millennial customers who are the primary target of Islamic banking services. This is a quantitative research using an associative approach. Primary data were collected through questionnaires distributed to 100 respondents using purposive sampling technique. The research instruments were tested for validity and reliability. Data analysis was conducted using multiple linear regression with SPSS version 21. The results showed that partially, product innovation had a significant effect on saving interest, as did service innovation, which positively contributes to increasing customer interest. The coefficient of determination (R²) value of 71.9% indicates that product and service innovation variables simultaneously explain the variability in saving interest. The conclusion of this study is that innovative strategies implemented by Islamic banks, both in terms of product development and digital service enhancement, significantly influence millennials' saving interest. These findings imply that Islamic banks need to continuously strengthen innovation elements to maintain and improve millennial customer loyalty in today’s digital era.